Experience of Weak Soil Reinforcement by Soil-Cement Elements Manufactured by Deep Soil Mixing Technology - Zotsenko, Mykola; ., Yuriyvynnykov; Kharchenko, Maksym (International Journal of Engineering and Technology, 2018)
Problematic issues of construction and operation in complex geotechnical conditions are systematized (subsiding and peaty soil, silt, filled, man-made soil, saturated, land sliding and seismically hazardous territories, densely developed areas) by the means of reinforcing soil massif by vertical soil-cement elements (SCE) using deep soil mixing (DSM) technology. The practical solution experience of highly efficient â€œman-made soil-cement base â€“ foundation â€“ structureâ€ systems is shown by the example of complex geotechnical conditions under static and dynamic influences (including earthquakes and critical failure man-made loads), and excavation using SCE. A decreasing in a settlement of soil-cement bases of buildings by 2 â€“ 4 times compared to natural soil massif and increasing in soil-cement mechanical features by 2.5 times has been established. The options of decreasing the seismic hazard (increasing the seismic stability of soil) for securing the emergency-free operation of oil storage vertical steel tank in case of the varying intensity earthquakes utilizing the man-made soil-cement base has been justified.Â Â
Keywords: complex geological conditions; soil-cement element; weak soil; settling; strength; seismic stability; vertical steel tank; calculation scheme.